FILSAFAT PENDIDIKAN ISLAM DALAM KAJIAN; SEJARAH FILSAFAT ILMU - Suhari Suhari (ADIBA : JOURNAL OF EDUCATION, 2025)
This article discusses the historical development of the philosophy of science in three main periods: the ancient Greek era, the medieval era, and the modern era. Each period has unique characteristics that reflect the paradigm shift in understanding science, from speculative approaches to systematic scientific methods. This study uses a descriptive qualitative method with a historical approach to analyze the development of philosophical thought based on the main works of philosophers in each era. The results show significant evolution in scientific methods and approaches, connecting the tradition of metaphysical speculation with modern empirical methods.